PERSONALITY TYPE D AND THE LEVEL OF SUBCLINICAL INFLAMMATION MARKERS IN CHD PATIENTS - A. N. Sumin; A. V. Osokina; N. V. Fedorova; O. I. Rajh; O. N. Hrjachkova; O. L. Barbarash (Российский кардиологический журнал, 2016)
Aim. To study the level of biomarkers of subclinical inflammation in CHD patients with existence of absence of personality type D.Material and methods. In 62 patients with stable CHD before planned CBG operation we assessed concentrations: of matrix metalloproteases -2, -3, -9, tissue inhibitor of matrix proteases -1, -2, C-reactive protein, soluble CD40 ligand, tumor necrosis factor alpha. For further study we selected two groups: 1 group (n=27) — patients with type D and 2 group (n=35) — with non-D type. Personality type was defined with DS-14 questionnaire. Patients were asked 14 questions with 5 variants of responses to each. Counting of points was done by two scales: negative irritability and social suppression. Type D was set if 10 points and more by each of the scales. All patients underwent: general and biochemical blood tests, echocardiography, color duplex scanning of brachiocephalic arteries and coronary angiography.Results. In intergroup comparison both groups were comparable by the most anamnestic and clinical parameters. There were no any differences in the instrumental assessments data. In type D patients there was higher level of MMP-9 (resp. 53,2 pg/mL and 66,5 pg/mL; р=0,051) and sCD40L (resp. 2,8 ng/mL and 5,7 ng/mL; р=0,013) comparing with those non-D-type. The level of other biomarkers in groups did not differ, concentration of MMP-2 and TNF-α were slightly higher among type-D, of the others — among non-D-typers. There were also statistically significant negative correlations of type-D and MMP-9 and sCD40L.Conclusion. In CHD patients, examined before coronary bypass operation, presence of type D personality was not followed by the increase of subclinical inflammation markers level comparing to patients without such type. In type-D patients there was increase of platelet activation markers activation, that associates with adverse outcomes in CHD.